2015
DOI: 10.14336/ad.2014.0330
|View full text |Cite
|
Sign up to set email alerts
|

Hypoglycemia in Older People - A Less Well Recognized Risk Factor for Frailty

Abstract: Recurrent hypoglycemia is common in older people with diabetes and is likely to be less recognized and under reported by patients and health care professionals. Hypoglycemia in this age group is associated with significant morbidities leading to both physical and cognitive dysfunction. Repeated hospital admissions due to frequent hypoglycemia are also associated with further deterioration in patients' general health. This negative impact of hypoglycemia is likely to eventually lead to frailty, disability and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
216
2
18

Year Published

2016
2016
2017
2017

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 252 publications
(239 citation statements)
references
References 75 publications
3
216
2
18
Order By: Relevance
“…Additional longitudinal studies have revealed that diabetes increases the risk for frailty in older adults (60 years or more) (García-Esquinas et al, 2015a). Importantly, hypoglycemia, which is common in older people with diabetes, is also associated with physical and cognitive dysfunction in this population, being this association related to under nutrition (Abdelhafiz et al, 2015). In addition to the associated comorbidities, a direct effect of diabetes on skeletal muscle seems to contribute to mobility reduction process in older individuals with diabetes (Kalyani et al, 2014).…”
Section: Diabetesmentioning
confidence: 99%
“…Additional longitudinal studies have revealed that diabetes increases the risk for frailty in older adults (60 years or more) (García-Esquinas et al, 2015a). Importantly, hypoglycemia, which is common in older people with diabetes, is also associated with physical and cognitive dysfunction in this population, being this association related to under nutrition (Abdelhafiz et al, 2015). In addition to the associated comorbidities, a direct effect of diabetes on skeletal muscle seems to contribute to mobility reduction process in older individuals with diabetes (Kalyani et al, 2014).…”
Section: Diabetesmentioning
confidence: 99%
“…Published data on the prevalence of frailty Hypoglycaemia and frailty -risk factors, complications and consequences (Abdelhafiz et al[24]). …”
mentioning
confidence: 99%
“…Los pacientes ancianos con diabetes son especialmente vulnerables a la hipoglucemia debido a la coexistencia habitual de varios factores de riesgo: cambios en los mecanismos reguladores asociados al propio proceso de envejecimiento, comorbilidades como la insuficiencia renal, medicación múltiple que aumenta tanto la presencia de interacciones como de falta de adherencia al tratamiento, mayor duración de la diabetes, automonitorización infrecuente y falta de educación diabetológica (tabla 3) 1,8,27,28 .…”
Section: Hipoglucemiaunclassified